Foot defects in infants and children and three-plane manual therapy - Monika Joanna Stecko; Agata Wawryków; Katarzyna Korabiusz; Anna Fabian-Danielewska; Inga Janik (Kazimierz Wielki University, 2018)
The subject of the article are foot defects in infants and children as well as early diagnosis and application of three-plane manual therapy of foot defects in children. Foot defects in infants and children are a common problem and the examination of the correctness of foot is very importan. Three-plane manual therapy of foot defects in children is one of the proposals that can be used in small patients because it brings therapeutic effects. Rapid implementation of therapy, gives us the ability to inhibit abnormal movement patterns and seek to the correct distribution of muscle tone